Rancang Bangun Sistem Peringatan Dini Risiko Longsor dan Gempa Berbasis ESP32 dan Firebase Realtime Database dengan Kendali Alarm Bertingkat - Fauzi Bondan Prihananto; Erlangga Bayu Yudho Prakoso; Tomy Anugerah Islami; Pramono (Jurnal Riset Multidisiplin Edukasi, 2026)
This article presents the development of an ESP32 and Firebase Realtime Database-based early warning system for landslide and earthquake risks. The main emphasis is placed on a multi-level alarm control mechanism rather than sensor monitoring only. The prototype employs an ADXL345 to capture tilt and vibration data, a Capacitive Soil Moisture Sensor to read soil moisture conditions, an ESP32 as the controller, Firebase as the real-time synchronization medium, a web dashboard as the monitoring interface, and a buzzer as the warning actuator. Sensor data are processed into SAFE, WARNING, and DANGER levels, enabling the system to produce different alarm responses according to the detected risk level. The dashboard provides data visualization, threshold configuration, event recording, device health monitoring, and administrator commands through Firebase. Testing was conducted by changing the ADXL345 position, applying vibration simulations, and comparing soil moisture value variations. The results indicate that the device can acquire sensor data, update Firebase records, display information on the dashboard, and drive the buzzer according to the risk status. The proposed system can be used as a local early warning prototype that combines IoT integration and alarm response control for landslide and earthquake mitigation.